Factores asociados a la adherencia al tratamiento farmacológico en pacientes hipertensos atendidos en tres establecimientos del primer nivel de atención en Iquitos, Perú-2025 - Flores Saavedra, Luigi Daniel (2025)
Introduction: Hypertension represents one of the leading causes of morbidity and mortality worldwide. Lack of adherence to antihypertensive pharmacological treatment remains a significant issue, especially in regions with geographic and cultural limitations such as Loreto, Peru. This study aimed to determine the factors associated with adherence to pharmacological treatment among hypertensive patients attending three primary healthcare facilities in Iquitos, 2025. Methods: An observational, analytical, cross-sectional study was conducted among 340 hypertensive patients selected through stratified random sampling. The Morisky Green questionnaire was used to assess treatment adherence. Sociodemographic, clinical, and therapeutic variables were analyzed using Chi-square and Mann Whitney U tests, considering a significance level of p<0.05. Results: The median age was 64 years, 77.1% were women, and 77.6% were non-adherent to treatment. Adherence was higher among younger patients (p<0.001), women (p=0.04), and housewives (p=0.008). No significant association was found with BMI or comorbidities. Adherent patients showed lower systolic (122.5 ± 14.0 vs. 138.5 ± 13.6 mmHg) and diastolic blood pressure levels (81.9 ± 4.5 vs. 91.5 ± 12.1 mmHg) (p<0.001). Adherence decreased as the duration of diagnosis increased (p=0.02). Conclusions: Antihypertensive therapeutic adherence was low and was mainly associated with age, sex, occupation, and perceived blood pressure control. These findings highlight the need to strengthen educational and follow-up strategies at the primary care level to improve treatment compliance and prevent cardiovascular complications.